Effect of interactions between nickel and other heavy metals on the soil microbiological properties - J. Wyszkowska; E. Boros; J. Kucharski (Plant, Soil and Environment, 2007)
A pot greenhouse experiment was performed to determine the effect of contamination with nickel interacting with other heavy metals on the microbiological properties of soil. The study was conducted on samples of soils classified under natural conditions as typical Eutric Cambisol developed from heavy loamy sand and typical Eutric Cambisol developed from light silty loam. Soil material was contaminated with nickel in the amount of 50 and 200 mg Ni2+/kg. The treatments with 200 mg Ni2+/kg were additionally contaminated with other heavy metals (Zn2+, Cu2+, Pb2+, Cd2+, Cr6+), in the amount of 50 mg/kg soil. The following treatments, in which the soil was contaminated with heavy metals applied alone or in combinations, were compared in the study: Ni, Zn, Cu, Pb, Cd, Cr, NiZn, NiCu, NiPb, NiCd, NiCr, NiZnCu, NiZnPb, NiZnCd, NiZnCr, NiZnCuPb, NiZnCuCd, NiZnCuCr, NiZnCuPbCd, NiZnCuPbCr, NiZnCuPbCdCr. The experiment was carried out in four replications. A microbiological analysis was performed on days 28 and 56. The tested crop was oat. It was found that the impact of particular heavy metals on microbiological properties of soils depended on their type, interactions between nickel and zinc, copper, lead, cadmium and chromium (VI), date of analysis and soil species. Soil contamination with heavy metals reduced the population size of Azotobacter spp. The counts of other microbial groups, i.e. copiotrophic bacteria, spore-forming copiotrophic bacteria, oligotrophic bacteria, spore-forming oligotrophic bacteria, ammonifying bacteria, nitrogen immobilizing bacteria, cellulose-decomposing bacteria, Arthrobacter spp., Pseudomonas spp., actinomyces and fungi, showed varied susceptibility to heavy metals.